(untitled) (Orinoquia, 2021)
The constant investigation regarding the severe acute respiratory syndrome coronavirus 2 (SARSCoV-2) requires periodic reviews in which recent and relevant information is concentrated. The objective of this study was to carry out a systematic epidemiological review of SARS-CoV-2 in domestic dogs and cats, as well as the phylogenetic analysis of the genetic sequences of the virus isolated from dogs and cats around the world, reported on GISAID’s platform. This systematic review was structured based on the PRISMA protocol. The keywords used were: SARS-CoV-2, COVID-19, canines, felines, companion animals, animal reservoirs, and zoonoses. Additionally, all the genetic sequences of SARS-CoV-2 isolated from dogs and cats around the world, published in the "EpiCov" database of GISAID’s platform, were selected and analyzed through Nextclade’s platform for the generation of the respective phylogenetic trees. Regarding the results, the isolation of SARS-CoV-2 gene material in 99 dogs and 108 cats naturally infected with this virus has been reported worldwide. In addition, there is a global total of 133 genetic sequences of SARS-CoV-2 in domestic canines (45) and felines (88) reported in GISAID, where the variants of concern (VOC) (Alpha and Delta) and the variants of interest (Iota and Lambda) for public health according to the WHO, have been isolated. On the other hand, the viral lineage B.1. has been the most predominant in both canines and felines (13.3%) and the clades Nextstrain 19A (24.1%) and GISAID GH (32.3%) the most frequent, as well as North America the region with the highest number of SARS-CoV-2 genomes isolated from domestic canines and felines (40.1%). In conclusion, domestic canines and felines are susceptible to SARS-CoV-2 infection, probably due to a spillover effect from humans. Due to their low capacity to transmit the virus to other animal species, companion animals can be considered epidemiological dead-end hosts in the virus transmission dynamics. Finally, that the VOC Alpha and Delta were able to infect both dogs and cats, is an obviously significant finding for global public health and knowledge of the epidemiological dynamics of this new virus.